Effect of clover sprouts protein hydrolysates as an egg substitute on physicochemical and sensory properties of mayonnaise. Issue 1 (6th December 2021) - Mirsadeghi Darabi, Dina; Ariaii, Peiman; Safari, Reza; Ahmadi, Mohammad
Abstract: Mayonnaise is a semi‐solid oil‐in‐water emulsion that in addition to eggs other stabilizers and thickeners are used as emulsifiers for better stability. Although eggs are an important ingredient in the production of mayonnaise, the health problems associated with the use of eggs is increasing due to their high cholesterol content. The aim of this study was to evaluate the feasibility of clover sprout protein hydrolysates (CSPH) to replace eggs for the production mayonnaise. First, CSPH was produced using alcalase and flavourzyme enzyme, and in order to find the best enzyme, the degree of hydrolysis (DH) and protein recovery (PR) were determined. Then four mayonnaise treatments included, T1: control (egg 9%), T2: egg 6%+ CSPH 3%, T3: egg 3%+ CSPH 6%, T4: egg 0%+ CSPH 9% was prepared and the stability, viscosity, physicochemical, textural, and sensory properties of mayonnaise was investigated. The samples containing CSPH showed that CSPH had high essential amino acids, CSPH from alcalase enzyme had higher amounts of protein, DH, PR, and increasing hydrolysis time had a positive effect on these parameters ( p  < .05); therefore, CSPH from alcalase enzyme was used for the production mayonnaise. The stability, viscosity, firmness, adhesion of texture, and pH increased with increasing CSPH, while the brightness, acidity, and sensory score of the samples decreased ( p  < .05). In general, T3 had an acceptable quality in terms of the studied characteristics, but sensory score in T4 could not be confirmed. Hence, by replacing eggs with CSPH up to 6%, mayonnaise with appropriate physicochemical and sensory properties can be produced. Therefore, the formulation egg 3%+ CSPH 6% is an appropriate choice to produce mayonnaise for consumers who are on a restricted diet to eat foods containing eggs. Abstract : Mayonnaise is an oil‐in‐water emulsion that in addition to eggs other stabilizers and thickeners are used as emulsifiers for better stability. Although eggs are an important ingredient in the production of mayonnaise, the health problems associated with the use of eggs is increasing due to their high cholesterol content. The aim of this study was to evaluate the feasibility of clover sprout protein to replace eggs for the production mayonnaise. The results indicate that using clover protein up to 6% can satisfactorily remove most of the mayonnaise egg and produce low‐egg mayonnaise, thus producing a functional product and preventing the side effects of egg yolk consumption.